2022
DOI: 10.3389/frph.2022.780157
|View full text |Cite
|
Sign up to set email alerts
|

Developing a sexual and reproductive health educational intervention for adolescent Syrian refugee girls: Challenges and lessons learned

Abstract: In Lebanon, a country with the highest per capita refugee population in the world, roughly one in four persons is forcibly displaced. Early marriage is highly prevalent among Syrian refugees in Lebanon and qualitative studies suggest an unmet need for sexual and reproductive health (SRH) information and services in this community. Adolescent Syrian refugee girls in Lebanon are a vulnerable population at risk of negative SRH outcomes related to early sexual debut, which occurs primarily in the context of early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Our findings emphasize the importance of including mothers in SRH educational interventions in this community, focusing not only on providing correct information but also on improving communication, which may translate into safer practices among adolescents [45]. Indeed, the Amenah intervention includes a dedicated component for mothers which focuses on destigmatizing SRH and improving maternal-daughter communication around menstruation and other SRH topics [46].…”
Section: Plos Global Public Healthmentioning
confidence: 70%
See 1 more Smart Citation
“…Our findings emphasize the importance of including mothers in SRH educational interventions in this community, focusing not only on providing correct information but also on improving communication, which may translate into safer practices among adolescents [45]. Indeed, the Amenah intervention includes a dedicated component for mothers which focuses on destigmatizing SRH and improving maternal-daughter communication around menstruation and other SRH topics [46].…”
Section: Plos Global Public Healthmentioning
confidence: 70%
“…Many of these determinants, such as humanitarian crises, extreme poverty, and early marriage are societal-and community-based drivers of health which are beyond the scope of this current work. Notably, however, the Amenah intervention does explicitly address several of these issues, including patriarchal gender norms, drivers of early marriage, access to health services, stigma around girls' SRH and adolescent disempowerment [46]. Finally, due to gender norms and stigmatization of premarital sex, we were only able to measure knowledge, rather than attitudinal or behavioral outcomes, though studies elsewhere have shown that SRH knowledge in adolescence may be protective against high-risk sexual practices in adulthood [48,49].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Therefore, larger investment in community support groups, peer-educators and interpreters will not only improve may improve HIV/STI and other sexual health disparities [59,86]. Developing supportive environments through peer-led advocacy and provider sensitivity training could help produce long-term, sustainable improvements to sexual health while at the same time, enhance sex equity [88–90].…”
Section: Discussionmentioning
confidence: 99%